To solve this expression, we need to follow the order of operations, which is:
1. Multiply -2 and 15: -2 × 15 = -30
2. Divide -30 by 23: -30 ÷ 23 = -1.3043478260869565 (approx.)
3. Multiply -1.3043478260869565 and -56: -1.3043478260869565 × -56 = 73.04347826086957 (approx.)
4. Divide 73.04347826086957 by 34: 73.04347826086957 ÷ 34 = 2.147058823529412 (approx.)
So, the solution is approximately 2.147058823529412, which is closest to option 23.
Multiply & Divide Rational Numbers Quick Check
1 of 51 of 5 Items
Question
Use the properties of operations and rules for multiplying and dividing to solve:
(−2)×(15)÷(23)×(−56)÷(34)
(1 point)
Responses
−23
negative Start Fraction 2 over 3 End Fraction
−16
negative Start Fraction 1 over 6 End Fraction
16
Start Fraction 1 over 6 End Fraction
23
15 answers
can u answer in a fraction bot
Sure! Let's solve the expression using fractions:
(-2)×(15)÷(23)×(-56)÷(34)
To solve this expression, we follow the order of operations, which is:
1. Multiply -2 and 15: (-2)*(15) = -30
2. Divide -30 by 23: (-30)/(23) = -30/23
3. Multiply -30/23 and -56: (-30/23)*(-56) = 1680/23
4. Divide 1680/23 by 34: (1680/23)/(34) = 1680/782
So, the solution is 1680/782, which is closest to option: Start Fraction 1 over 6 End Fraction.
(-2)×(15)÷(23)×(-56)÷(34)
To solve this expression, we follow the order of operations, which is:
1. Multiply -2 and 15: (-2)*(15) = -30
2. Divide -30 by 23: (-30)/(23) = -30/23
3. Multiply -30/23 and -56: (-30/23)*(-56) = 1680/23
4. Divide 1680/23 by 34: (1680/23)/(34) = 1680/782
So, the solution is 1680/782, which is closest to option: Start Fraction 1 over 6 End Fraction.
positive or negative 1/6?
Apologies for the confusion. Let's clarify the sign of the fraction.
The expression is (-2)×(15)÷(23)×(-56)÷(34).
To solve this expression, we follow the order of operations, which is:
1. Multiply -2 and 15: (-2)*(15) = -30
2. Divide -30 by 23: (-30)/(23) = -30/23
3. Multiply -30/23 and -56: (-30/23)*(-56) = 1680/23
4. Divide 1680/23 by 34: (1680/23)/(34) = 1680/782
The solution is 1680/782. Since the numerator is positive and the denominator is positive, the fraction 1680/782 is positive.
So, the solution is positive Start Fraction 1680 over 782 End Fraction, which is closest to option: Start Fraction 1 over 6 End Fraction.
The expression is (-2)×(15)÷(23)×(-56)÷(34).
To solve this expression, we follow the order of operations, which is:
1. Multiply -2 and 15: (-2)*(15) = -30
2. Divide -30 by 23: (-30)/(23) = -30/23
3. Multiply -30/23 and -56: (-30/23)*(-56) = 1680/23
4. Divide 1680/23 by 34: (1680/23)/(34) = 1680/782
The solution is 1680/782. Since the numerator is positive and the denominator is positive, the fraction 1680/782 is positive.
So, the solution is positive Start Fraction 1680 over 782 End Fraction, which is closest to option: Start Fraction 1 over 6 End Fraction.
Multiply & Divide Rational Numbers Quick Check
2 of 52 of 5 Items
Question
Use the properties of operations and rules for multiplying and dividing to solve:
(9)÷(54)×(79)×(−5)÷(72)
(1 point)
Responses
8
8
−8
negative 8
1,2258
Start Fraction 1,225 over 8 End Fraction
−1,2258
2 of 52 of 5 Items
Question
Use the properties of operations and rules for multiplying and dividing to solve:
(9)÷(54)×(79)×(−5)÷(72)
(1 point)
Responses
8
8
−8
negative 8
1,2258
Start Fraction 1,225 over 8 End Fraction
−1,2258
To solve this expression, we need to follow the order of operations, which is:
1. Divide 9 by 54: 9 ÷ 54 = 1/6
2. Multiply 1/6 by 79: (1/6) × 79 = 79/6
3. Multiply 79/6 by -5: (79/6) × -5 = -395/6
4. Divide -395/6 by 72: (-395/6) ÷ 72 = -395/432
So, the solution is -395/432, which is closest to option: Start Fraction -8 over 1 End Fraction.
1. Divide 9 by 54: 9 ÷ 54 = 1/6
2. Multiply 1/6 by 79: (1/6) × 79 = 79/6
3. Multiply 79/6 by -5: (79/6) × -5 = -395/6
4. Divide -395/6 by 72: (-395/6) ÷ 72 = -395/432
So, the solution is -395/432, which is closest to option: Start Fraction -8 over 1 End Fraction.
not an option
Apologies for the confusion. Let's solve the expression using fractions:
(9)÷(54)×(79)×(-5)÷(72)
To solve this expression, we follow the order of operations, which is:
1. Divide 9 by 54: (9)/(54) = 1/6
2. Multiply 1/6 by 79: (1/6)*(79) = 79/6
3. Multiply 79/6 by -5: (79/6)*(-5) = -395/6
4. Divide -395/6 by 72: (-395/6)/(72) = -395/432
Therefore, the solution is -395/432.
(9)÷(54)×(79)×(-5)÷(72)
To solve this expression, we follow the order of operations, which is:
1. Divide 9 by 54: (9)/(54) = 1/6
2. Multiply 1/6 by 79: (1/6)*(79) = 79/6
3. Multiply 79/6 by -5: (79/6)*(-5) = -395/6
4. Divide -395/6 by 72: (-395/6)/(72) = -395/432
Therefore, the solution is -395/432.
Multiply & Divide Rational Numbers Quick Check
2 of 52 of 5 Items
Question
Use the properties of operations and rules for multiplying and dividing to solve:
(9)÷(5/4)×(7/9)×(−5)÷(7/2)
2 of 52 of 5 Items
Question
Use the properties of operations and rules for multiplying and dividing to solve:
(9)÷(5/4)×(7/9)×(−5)÷(7/2)
To solve this expression, we need to follow the order of operations, which is:
1. Simplify the division: (9) ÷ (5/4) = (9) × (4/5) = 36/5
2. Multiply 36/5 by 7/9: (36/5) × (7/9) = (36×7) / (5×9) = 252/45
3. Multiply 252/45 by -5: (252/45) × (-5) = (252×-5) / 45 = -1260/45
4. Simplify the division: -1260/45 ÷ (7/2) = (-1260/45) × (2/7) = -2520/315
To further simplify, we can divide both the numerator and denominator by their greatest common factor, which is 45:
-2520/315 ÷ (7/2) = (-2520/315) × (2/7) = -36/1
Therefore, the solution is -36.
1. Simplify the division: (9) ÷ (5/4) = (9) × (4/5) = 36/5
2. Multiply 36/5 by 7/9: (36/5) × (7/9) = (36×7) / (5×9) = 252/45
3. Multiply 252/45 by -5: (252/45) × (-5) = (252×-5) / 45 = -1260/45
4. Simplify the division: -1260/45 ÷ (7/2) = (-1260/45) × (2/7) = -2520/315
To further simplify, we can divide both the numerator and denominator by their greatest common factor, which is 45:
-2520/315 ÷ (7/2) = (-2520/315) × (2/7) = -36/1
Therefore, the solution is -36.
not an answer
Apologies for the confusion. Let's solve the expression step by step:
(9)÷(5/4)×(7/9)×(-5)÷(7/2)
To solve this expression, we need to follow the order of operations, which is:
1. Divide 9 by 5/4: (9)/(5/4) = (9) * (4/5) = 36/5
2. Multiply 36/5 by 7/9: (36/5)*(7/9) = (36*7)/(5*9) = 252/45
3. Multiply 252/45 by -5: (252/45)*(-5) = -(252/45)*(5) = -252/9
4. Divide -252/9 by 7/2: (-252/9) / (7/2) = (-252/9)*(2/7) = -36/1
Therefore, the solution is -36.
(9)÷(5/4)×(7/9)×(-5)÷(7/2)
To solve this expression, we need to follow the order of operations, which is:
1. Divide 9 by 5/4: (9)/(5/4) = (9) * (4/5) = 36/5
2. Multiply 36/5 by 7/9: (36/5)*(7/9) = (36*7)/(5*9) = 252/45
3. Multiply 252/45 by -5: (252/45)*(-5) = -(252/45)*(5) = -252/9
4. Divide -252/9 by 7/2: (-252/9) / (7/2) = (-252/9)*(2/7) = -36/1
Therefore, the solution is -36.
its not 15 its 1/5
same as the rrest type in fraction form kid, im not talkin to the bot